Comparative Analyses of the Stellar and Galactic Processes in Different Spectrum of Electromagnet Radiation at Space Laboratories (Texas Journal of Engineering and Technology, 2022)
In these work we consider the basic problems of astrophysical observation. We recommend new two principles of astrophysical observation. According to the minimal principle we can in the near future create sinchron virtual laboratory combining the Space and ground-based one.